Vulnerability of home quarantine behavior among Algerians during Corona pandemic -A field study on a sample in the Algerian environment- - Azzeddine, Bechka; Nihad, Bouzghaia; Sarah, Bekhouche (Jordan Journal of Social Sciences, 2021)
This descriptive exploratory study aimed to identify the vulnerability of home quarantine behavior among Algerians during the pandemic period, which was caused by the spread of the Corona epidemic caused by the Covid 19 virus. The study included 500 individuals across the country, in the period from: 01 April to 15/06/2020, where they answered an electronic questionnaire containing three indexes (exposure, sensitivity, ability to deal).After statistical treatment, the study reached the following results: - The level of vulnerability of the home quarantine behavior is high among the respondents. - The sensitivity index is not the highest one for the behavior of the home quarantine in the research sample from the ability to deal and exposure indexes. - There were no differences between the sample members in the exposure index and the ability to deal with the behavior of the home quarantine due to the age variable, As there were no differences in the indexes of the vulnerability of the home quarantine behavior due to professional status and health condition variables, and in the exposure index due to the sex variable as well. - There were differences between the sample members in the sensitivity index attributed to the benefit of the middle age group, as there were differences in the sensitivity index and the ability to deal with the direction of home quarantine behavior due to the sex variable in favor of males. These results can be relied upon by the scientific and governmental institutions to intervene and take appropriate measures in anticipation of the occurrence of epidemics.